The effects of lower limb wearable resistance on sprint running performance: A systematic review. Issue 3 (15th March 2020) - Feser, Erin H.; Macadam, Paul; Cronin, John B.
ABSTRACT: The aim of this review was to examine the literature that has used lower limb wearable resistance (WR) during sprint running. A systematic search was completed to identify acute and longitudinal studies assessing the effects of lower limb WR on sprint running performance from international peer-reviewed journals. The Boolean phrases (limb OR leg OR lower extremity) AND (sprint*) AND (resist* OR weight OR load*) were used to search PubMed, SPORTDiscus, and Web of Science electronic databases. Ten studies met the inclusion criteria and were retained for analysis that reported the acute kinematic and kinetic effects ( n = 8), acute performance effects ( n = 3), and longitudinal effects ( n = 1). Results showed that the WR micro-loading (0.6–5% body mass) significantly increased contact time (2.9–8.9%), decreased step frequency (−1.4 to −3.7%), and slowed total sprint times (0.6–7.4%). Unloaded sprinting immediately following sprints with lower limb WR resulted in no significant change to total sprinting times. One longitudinal training study did not find a significant effect on maximal sprinting speed for non-trained participants. It can be concluded that not all step kinematic variables are affected during sprinting with an added load up to 5% body mass. Therefore, coaches can use lower limb WR to selectively overload certain aspects of sprint running, in particular stride frequency. It also appears that lower limb WR overloads sprint movement velocity and may provide a stimulus to increase horizontal force output, therefore, it may be inferred that lower limb WR has the potential to elicit improved sprinting performance.